Analyzing the Impact of Social Media and SEO on Sales Growth for Mandjha Ivan Gunawan Products - Andriani, Nur; Priadi , M. Dadi; Yuniarsih, Yuyun; Sabila, Silsi (Yayasan Sinergi Kawula Muda, 2024)
In the digital era, digital marketing has become increasingly important for expanding market share and boosting sales for companies. The aim of this study is to analyze the impact of digital marketing on sales growth and identify barriers to its implementation. PT Ivan Cipta Mukti Perkasa is one of the companies in the fashion industry owned by a renowned Indonesian designer, which sells women's Muslim clothing. This type of research is qualitative with a descriptive approach. Data collection techniques were conducted through interviews, observations, and documentation from sources at PT Ivan Cipta Mukti Perkasa. The results of this study indicate that PT Ivan Cipta Mukti Perkasa has implemented digital marketing well, but has not yet fully utilized all types of digital marketing. In this study, PT Ivan Cipta Mukti Perkasa has applied various digital marketing strategies in running its business, such as the use of websites, social media marketing, SEO, and advertising. The results of the implementation of digital marketing have successfully had a positive impact on sales growth. However, several barriers were also identified in the implementation of digital marketing.